LIFE SKILLS AS A PART OF BOARDING SCHOOL GRADUATES’ SOCIAL COMPETENCE - Koval, H. (Вісник Черкаського національного університету імені Богдана Хмельницького. Серія: "Педагогічні науки", 2017)
The article deals with life skills as part of boarding school graduates’ social competence. It is confirmed that to solve the problem of social competence after leaving the orphanage, it is necessary to take a number of measures aimed at the formation of life skills among graduates. Children from the orphanage do not have an adequate level of social competence, they do not ready for life in society; they have inaccurate preventive knowledge, distorted personal development: aggressive, emotionally unstable, impulsive, egocentric; they do not have the habit of self-analysis, they have low level of self-esteem; these children are not able to make decisions, plan their actions and be responsible for them. Strict regulation of regime includes the possibility of formation the affective behavior skills’ these children. That is why the formation of life skills should be the goal of educational programs and the core of socialization. As graduates of boarding school to get into a specific form of being community, to which the person belongs, painlessly adapt to it and in it, you must: have a certain amount of purposefully arranged information that allows you to create your image and prototype of objective reality; take freedom as a perceived necessity, as the possibility of relying on high-quality social information, to realize a personal choice of behavior; understand the diversity of the modern world and its contradictions; learn to make the right decision. All this allows people to achieve social intelligence, which is the derived result of social competence. Life skills formation is aimed at teaching people the ability to build a decent life, manage it and bear personal responsibility for it. Exactly in this sense, there is a life skills link with social competence, considering its first component. The concept of forming life skills and viable individual social competence can be seen as an integral component and as one of the viable ways of their achieving relatively marginalized population groups, which sometimes include graduates of boarding schools. Since the individual life skills based on a broad (public) vision of the world, the relationship in it, have systemic character, the process of their formation involves first of all information, i.e. the mastering by a student a certain amount of social information, its timely obtaining and credible character.